2013
DOI: 10.1590/s1806-37132013000500007
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria and follow-up in neuroendocrine cell hyperplasia of infancy: a case series

Abstract: Objective: Neuroendocrine cell hyperplasia of infancy (NEHI) is a form of childhood interstitial lung disease characterized by tachypnea, retractions, crackles, and hypoxia. The aim of this study was to report and discuss the clinical, imaging, and histopathological findings in a series of NEHI cases at a tertiary pediatric hospital, with an emphasis on diagnostic criteria and clinical outcomes. Methods: Between 2003 and 2011, 12 full-term infants were diagnosed with NEHI, based on clinical and tomographic fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 25 publications
0
44
0
7
Order By: Relevance
“…Some patients, however, have additional CT abnormalities, such as consolidation, bronchial wall thickening, and interlobular septal thickening. Sometimes ground-glass opacities are absent or have a different distribution (3,6,7,21). With regard to biopsy-proven PIG, the few published CT studies have shown mainly ground-glass opacities in a subsegmental, segmental, or diffuse distribution (11,15), very similar to what was found in NEHI (11): interlobar septal thickening or scarring, hyperinflation, air trapping, multifocal atelectasis (7), and multiple air-filled cystic changes of variable size (12).…”
mentioning
confidence: 87%
“…Some patients, however, have additional CT abnormalities, such as consolidation, bronchial wall thickening, and interlobular septal thickening. Sometimes ground-glass opacities are absent or have a different distribution (3,6,7,21). With regard to biopsy-proven PIG, the few published CT studies have shown mainly ground-glass opacities in a subsegmental, segmental, or diffuse distribution (11,15), very similar to what was found in NEHI (11): interlobar septal thickening or scarring, hyperinflation, air trapping, multifocal atelectasis (7), and multiple air-filled cystic changes of variable size (12).…”
mentioning
confidence: 87%
“…9,19,[26][27][28][29][30][31][32][33][34][35][36][37] A primary advance in this area is the growing recognition that NEHI can be diagnosed by using a chest CT scan without the need for lung biopsy. Brody et al 9 first fully described the radiologic features of NEHI in 2010.…”
Section: Neuroendocrine Cell Hyperplasia Of Infancymentioning
confidence: 99%
“…NEHI is not a life-threatening condition and most patients show clinical and radiographic improvement, especially after two years of age. However, some patients require supplemental oxygen for months to years, and air trapping and exercise intolerance may persist into adolescence (Deterding 2010;Gomes et al 2013). The development of nonatopic asthma has also been reported in follow-up (Lukkarinen et al 2013).…”
Section: Neuroendocrine Cell Hyperplasia Of Infancymentioning
confidence: 99%
“…A frontal CXR (c) obtained at 3 years of age shows continued pulmonary hyperinflation always reliable, especially if airway sampling is limited in the biopsy specimen . A presumptive diagnosis of NEHI can be made without lung biopsy if the clinical presentation and the findings on CT or pulmonary function testing are characteristic (Deterding 2010;Young et al 2010;Brody et al 2010;Kerby et al 2013;Gomes et al 2013). …”
Section: Neuroendocrine Cell Hyperplasia Of Infancymentioning
confidence: 99%